Effect of Siderophore on Iron Availability in a Diatom and a Dinoflagellate Species: Contrasting Response in Associated Bacteria - Sanchez, Nicolas; Brown, Eunice A.; Olsen, Yngvar; Vadstein, Olav; Iriarte, Jose L.; Gonzalez, Humberto E.; Ardelan, Murat Van (Frontiers in Marine Science, 2018)
Organic ligands play a key role controlling trace metal bioavailability in the world oceans, yet the species-specific requirements determining whether certain iron forms can be metabolized largely remain unclear. Siderophores are considered relevant within this pool of ligands keeping iron soluble. We used desferrioxamine B (DFB) to study the siderophore effect on cultures of Skeletonema costatum and Alexandrium catenella. The experimental approach used semi-continuous additions of iron(II) and DFB over time, reaching final concentrations of 1 and 10 nM Fe and 10-10000 nM DFB. The negative effect of DFB over growth in S. costatum was evident and sharp until day 9 for treatments above 500 nM. Delayed growth occurred at 10000 nM, reaching ~ 80 % of cell density in Controls under both iron conditions. A. catenella exhibited a more attenuated negative effect of DFB over growth, only significant at 10000 nM, while growth was enhanced at lowest DFB. Total bacterial abundance in diatom and dinoflagellate cultures presented inversed trends. While negatively correlated to DFB in diatom cultures, bacteria in high DFB treatments in dinoflagellate cultures reached highest abundances. Delayed growth exhibited in S. costatum at the highest DFB, indicates favorable changes for Fe uptake occurred over time, suggesting involvement of other mechanism facilitating the diatom cell membrane reduction. Overall unaffected growth in A. catenella suggests the potential to utilize FeDFB and therefore capacity to access strongly complexed Fe sources. Contrasting responses in the bacterial community associated with each species, highlight the complexity of these interactions, while suggest that for A. catenella it may represent an advantage for acquiring Fe. The DFB effect exhibited the capacity for different uptake strategies among phytoplankton species of different functional groups and underlines the necessity to broaden the study of iron bioavailability on a species basis, alongside interaction with other microbial components such bacteria, to reflect interactions in natural ecosystems.